Intercalation of Diverse Organic Guests into Layered Europium Hydroxides – Structural Tuning and Photoluminescence Behavior. Issue 3 (12th December 2013) - Gu, Qingyang; Chu, Nankai; Pan, Guohua; Sun, Genban; Ma, Shulan; Yang, Xiaojing
Abstract: Organic anions of two benzenepolycarboxylic acids [1, 3, 5‐benzenetricarboxylic acid (BTA) and 2, 2′‐biphenyldicarboxylic acid (BDA)], two pyridinecarboxylic acids [quinolinic acid (QA) and 2, 5‐pyridinedicarboxylic acid (PDA)], and two amino acids [phenylalanine (Phe) and tyrosine (Tyr)] were intercalated into the galleries of NO3 – ‐type layered europium hydroxide (NO3 –LEuH). All the prepared products displayed XRD patterns with series of diffractions due to layered materials. The composite structures and the arrangement of the guests in the galleries were investigated in detail. The structure of the organic guests (such as the number and position of carboxyl groups) affects the arrangement in the interlayer. SEM observations showed that the NO3 –LEuH precursor and its intercalates crystallize in a columnar or layered stacking structure composed of hexagonal thin platelets. The luminescence study indicated that all samples display the typical red emission of Eu 3+ . Efficient energy transfer between intercalated BTA/BDA anions and Eu 3+ centers takes place, markedly enhancing the Eu 3+ luminescence, whereas QA–LEuH and PDA–LEuH with pyridinedicarboxylic acid anions show no obvious change in luminescence intensity. When amino acid anions such as Phe and Tyr were introduced into the interlayer, the Eu 3+ emission was strongly quenched. The simple soft chemical method can open great opportunities for developing organic–inorganic multifunctional luminescent materials or biological probes for detecting certain amino acids. Abstract : Organic anions of benzenepolycarboxylic acids [1, 3, 5‐benzenetricarboxylic and 2, 2′‐biphenyldicarboxylic acids (BTA and BDA)], pyridinecarboxylic acids [quinolinic and 2, 5‐pyridinedicarboxylic acids (QA and PDA)], and amino acids (Phe and Tyr) were intercalated into NO3 –LEuH. BTA and BDA markedly enhanced the Eu 3+ luminescence, QA and PDA had no obvious effect, while Phe and Tyr strongly quenched the emission.